Prospek Pengembangan Agroindustri Sagu di Riau Kepulauan - Dorlan Sipahutar; Herman Supriadi (Jurnal Sagu, 2009)
A survey on sago development in Riau Island Province had been conducted during May 2007 through PRA (Participatory Rural Apprasial). Primary data was collected from 20 farmers, 3 sago processing industries and 5 trader of sago mills, while secondary data was gathered from related institutions. The quantitative and qualitative data were analyzed using SWOT (strength, Weakness, Opportunity and Threat) Analysis. The analysis concludes that the strengths of sago industry development are: land suitability, farmer motivation, culture, and production continuity. The weakness of sago industry in Riau Island are: limited marketing acces and low processing technology adoption. Sago industry in Riau islands has great potential to be developed through strong government regulation and has high demand in the world market. While the threats are: The development of sago industry in other countries, trade monopoly of processed products, and lack of partnership systems. Strategic recommendation to develop sago industry in Riau Islands are: 1) Establishing land conservation and production, 2) Empowerment of farmer group for marketing and technology adoption, 3) Establishing stronger government regulation to develop sago industry and export, 4) Anticipating limited marketing and partnership system, as well as the improvement of agroindustry in other countries